Francisco Alba H. La población de México : evolución y dilemas. El Colegio de México, México, 1977. 187 p. - Tuirán, Rodolfo A. (Estudios Demográficos y Urbanos, 1977)
FRANCISCO ALBA H., La población de México: evolución y dilemas. El Colegio de México, México, 1977.